LPCAT3 deficiency in hematopoietic cells alters cholesterol and phospholipid homeostasis and promotes atherosclerosis. (August 2018) - Thomas, Charles; Jalil, Antoine; Magnani, Charlène; Ishibashi, Minako; Queré, Ronan; Bourgeois, Thibaut; Bergas, Victoria; Ménégaut, Louise; Patoli, Danish; Le Guern, Naig; Labbé, Jérôme; Gautier, Thomas; et al.
Abstract: Background and aims: LPCAT3 plays a major role in phospholipid metabolism in the liver and intestine. However, the impact of LPCAT3 on hematopoietic cell and macrophage functions has yet to be described. Our aim was to understand the functions of LPCAT3 in macrophages and to investigate whether LPCAT3 deficiency in hematopoietic cells may affect atherosclerosis development. Methods: Mice with constitutive Lpcat3 deficiency ( Lpcat3 −/− ) were generated. We used fetal hematopoietic liver cells to generate WT and Lpcat3 −/− macrophages in vitro and to perform hematopoietic cell transplantation in recipient Ldlr −/− mice. Results: Lpcat3 -deficient macrophages displayed major reductions in the arachidonate content of phosphatidylcholines, phosphatidylethanolamines and, unexpectedly, plasmalogens. These changes were associated with altered cholesterol homeostasis, including an increase in the ratio of free to esterified cholesterol and a reduction in cholesterol efflux in Lpcat3 −/− macrophages. This correlated with the inhibition of some LXR-regulated pathways, related to altered cellular availability of the arachidonic acid. Indeed, LPCAT3 deficiency was associated with decreased Abca1, Abcg1 and ApoE mRNA levels in fetal liver cells derived macrophages. In vivo, these changes translated into a significant increase in atherosclerotic lesions in Ldlr −/− mice with hematopoietic LPCAT3 deficiency. Conclusions: This study identifies LPCAT3 as a key factor in the control of phospholipid homeostasis and arachidonate availability in myeloid cells and underlines a new role for LPCAT3 in plasmalogen metabolism. Moreover, our work strengthens the link between phospholipid and sterol metabolism in hematopoietic cells, with significant consequences on nuclear receptor-regulated pathways and atherosclerosis development. Highlights: LPCAT3 controls arachidonic acid incorporation into glycerophospholipids in macrophages. Alteration of arachidonic acid availability inhibits LXR pathways such as cholesterol efflux in Lpcat3 −/− macrophages. LPCAT3 deficiency in hematopoieic cells promotes atherosclerosis development in recipient Ldlr −/− mice.